Cancer and autoimmunity - Shoenfeld, Yehuda, 1948-; Gershwin, M. Eric, 1946- (Autoantibody library., 2000)
Of the two disciplines in parallel development for two decades, tumor immunology and transplantation immunology, the latter has thrived and has led to some of the most critical discoveries in immunobiology. The former continues to thwart both scientists and clinicians alike. The goal of immunologists in modern day research is to develop a simple and effective means to manipulate cancer in vivo, possibly encompassing several venues: identifying a phenotypic marker and the use of either active or passive immunization; include the use of passive reagents carrying "warheads" to selectively destroy cancer cells; or altering the basic process of cell survival. This excellent multidiscipline-authored volume presents a theme which has not been well described before. The papers include both basic and clinical science and range from sophisticated molecular biology to little more than phenomenology (e.g. the increased association of cancer in some autoimmune diseases and increased presentation of autoimmune phenomena in malignant condition). This, however, is state-of-the-art. This collection of themes will be of use not only to bench scientists, but also to clinicians who treat patients. The book represents progress at the cutting edge of this discipline, and points the way to further developments in the "black box" of immunology